2008
DOI: 10.3748/wjg.14.4633
|View full text |Cite
|
Sign up to set email alerts
|

Lentivirus mediated shRNA interference targeting MAT2B induces growth-inhibition and apoptosis in hepatocellular carcinoma

Abstract: AIM:To investigate the effects of lentivirus vector mediated short hairpin RNA interference targeting methionine adenosyltransferase 2β gene (LV-shMAT2B) on hepatocellular carcinoma (HCC) cells. METHODS:We constructed four plasmids of RNA interference targeting the MAT2B gene. After LVshMAT2B was transfected with L-02 cells and two kinds of HCC cells, cell viability and proliferation were measured with MTT and [3H]thymidine assays respectively. Flow cytometry was used to assess cell apoptosis. The level of S-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
(32 reference statements)
1
10
0
Order By: Relevance
“…In addition, the transfection of miR-21-3p mimics increased intracellular SAM contents. Conflicting results have been reported on intracellular SAM contents increasing or decreasing after the knockdown of MAT2A in hepatoma cells [16][18], whereas, intracellular SAM contents were increased in all relevant studies after knockdown of MAT2B or both MAT2A and MAT2B [17][19]. Consistent with previous studies, our results showed that miR-21-3p directly reduced the expression of both MAT2A and MAT2B resulting in increasing intracellular SAM contents that have been proven to impair the growth of hepatoma cells.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In addition, the transfection of miR-21-3p mimics increased intracellular SAM contents. Conflicting results have been reported on intracellular SAM contents increasing or decreasing after the knockdown of MAT2A in hepatoma cells [16][18], whereas, intracellular SAM contents were increased in all relevant studies after knockdown of MAT2B or both MAT2A and MAT2B [17][19]. Consistent with previous studies, our results showed that miR-21-3p directly reduced the expression of both MAT2A and MAT2B resulting in increasing intracellular SAM contents that have been proven to impair the growth of hepatoma cells.…”
Section: Discussionsupporting
confidence: 85%
“…Because MAT2A and MAT2B play crucial role in facilitating the growth of hepatoma cells, they are valid targets for antineoplastic therapy. Recent studies have shown that silencing MAT2A and MAT2B by using small interfering RNA substantially suppress growth and induce apoptosis in hepatoma cells [16][19].…”
Section: Introductionmentioning
confidence: 99%
“…inhibition by downregulating cyclin D1. Moreover, apoptosis of HCC cells induced by LV-shRnA of MAT2B was involved in downregulating BCL-XL and upregulating BCL-XS (6). In both liver and colon cancers, MAT2B interacted with gIT1 and formed a scaffold to regulate Ras/Raf/MeK1/2 activity and therefore promoted cell growth and tumorigenesis (7,8).…”
Section: Lentivirus-mediated Downregulation Of Mat2b Inhibits Cell Prmentioning
confidence: 99%
“…Although MAT2B is known as a gene encoding regulatory subunit for changing MATII enzymatic activity, recent studies have reported that MAT2B also has several kinds of specific biologic fuctions, especially in cancer. MAT2B expression is elevated in human hepatocellular carcinoma and colon cancer which promotes the growth advantage or cell cycle of tumor cells (5)(6)(7)(8)(9). In HCC cells, MAT2B knockdown led to growth…”
Section: Introductionmentioning
confidence: 99%
“…In HCC, MAT gene expression is switched from MAT1A to MAT2A , accompanied by an induction of MAT2A and MAT2B protein levels [5,13,14]. This switch in MAT gene expression is proposed to facilitate the rapid cell growth and provide a proliferative advantage for cancer [15], and also makes MAT2A/MAT2B an attractive target for chemoprevention and treatment of HCC [16]. …”
Section: Introductionmentioning
confidence: 99%